Digital citizenship education at the early childhood level: how is it implemented? A systematic review - Lingxi Li; Jana Patricia M. Valdez; Yingqiao Du (International Journal of Child Care and Education Policy)
Abstract Users of technology are becoming younger over the years. Although the current generation of young children is often referred to as “digital natives,” this designation primarily reflects their intuitive engagement with digital tools rather than a comprehensive understanding of their responsible use. In contrast, fostering balanced, ethical, and safe digital behavior requires intentional education and support. This paper provides a systematic review of existing research on digital citizenship education in early childhood, aiming to clarify how core principles of digital citizenship are being introduced and implemented during the formative years. As digital citizenship education is not yet common at the ECE level, the main contribution of this study is the yielded insights, through in-depth analysis, on how digital citizenship education can be taught more effectively based on the gathered literature. The databases used for this systematic review were ProQuest Education, Web of Science, EBSCOhost, APA PsycInfo, ERIC, and Google Scholar. The related articles published until May 2024 were included in this review. Drawing on the PRISMA guidelines, we carefully selected 23 articles related to digital citizenship education for children 0 to 8 years old. Keywords were organized into two categories using the Boolean operator AND: (1) terms related to children (e.g., child*, preschool, kindergarten), and (2) “digital citizenship.” The findings demonstrate that the lessons towards digital citizenship can be more effective when integrated into core subjects with gamified and collaborative activities. The limitations and recommendations of the review are also discussed.